Fiscal Decentralization in the European Countries: A Cluster Analysis Approach - Alicja SEKULA; Kamila ADAMOWICZ (Communications of International Proceedings, 2021)
The scope of public authority depend on many factors. One of them is a declaration, usually expressed in the constitution of a given country (Sferlea, 2014, Libman, 2010, Nehmelman, Vetzo, 2016) of the application of the decentralisation principle in the performance of public tasks. Despite this declaration, the structure of the public sector and the tasks carried out at different levels in particular countries are not identical. This also applies to the countries of the European Union, although some issues related to legal order are regulated by treaties. This fact became a premise for undertaking the research presented in this article. Its aim was to compare the extent of fiscal decentralisation in EU countries, creation groups of states with similar levels of decentralization and then identify the characteristics of countries where the level is similar. Data obtained from Eurostat were subjected to statistical analysis – non-hierarchical grouping. For this purpose, the cluster analysis module of the R software was used. Analyse was made for the years 2013-2019 for 27 European countries. United Kingdom was excluded due to not available data in Eurostat for year 2019. Based on clustering, the following conclusions were drawn: the level of decentralization in the EU increases with the size of the country. Small states are centralized. Due to the second tier of government, federal countries are characterized by a small degree of decentralization, regardless of their size. The highest level of decentralization is in the Nordic countries, in Denmark so large that it formed a separate cluster.
Keywords: Decentralization; Public Finances; Local Government Autonomy; Public Expenditure; Public Revenue; European Union.